# Solve for j 24 = square root of j^2-(22-4)^2

24=j2-(22-4)2
Rewrite the equation as j2-(22-4)2=24.
j2-(22-4)2=24
Simplify each term.
Subtract 4 from 22.
j2-182=24
Raise 18 to the power of 2.
j2-1⋅324=24
Multiply -1 by 324.
j2-324=24
j2-324=24
Move all terms not containing j2 to the right side of the equation.
Add 324 to both sides of the equation.
j2=24+324
j2=348
j2=348
To remove the radical on the left side of the equation, square both sides of the equation.
j22=3482
Simplify each side of the equation.
Multiply the exponents in (j1)2.
Apply the power rule and multiply exponents, (am)n=amn.
j1⋅2=3482
Multiply 2 by 1.
j2=3482
j2=3482
Raise 348 to the power of 2.
j2=121104
j2=121104
Solve for j.
Take the square root of both sides of the equation to eliminate the exponent on the left side.
j=±121104
The complete solution is the result of both the positive and negative portions of the solution.
Simplify the right side of the equation.
Rewrite 121104 as 3482.
j=±3482
Pull terms out from under the radical, assuming positive real numbers.
j=±348
j=±348
The complete solution is the result of both the positive and negative portions of the solution.
First, use the positive value of the ± to find the first solution.
j=348
Next, use the negative value of the ± to find the second solution.
j=-348
The complete solution is the result of both the positive and negative portions of the solution.
j=348,-348
j=348,-348
j=348,-348
j=348,-348
Solve for j 24 = square root of j^2-(22-4)^2

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top